Nanoscale liposomal formulation of a SYK P-site inhibitor against B-precursor leukemia - Uckun, Fatih M.; Qazi, Sanjive; Cely, Ingrid; Şahin, Kazım; Shahidzadeh, Anoush; Ozercan, Ibrahim; Yiv, Seang (Amer Soc Hematology, 2013)
We report preclinical proof of principle for effective treatment of B-precursor acute lymphoblastic leukemia (ALL) by targeting the spleen tyrosine kinase (SYK)-dependent antiapoptotic blast cell survival machinery with a unique nanoscale pharmaceutical composition. This nanoscale liposomal formulation (NLF) contains the pentapeptide mimic 1,4-Bis (9-O dihydroquinidinyl) phthalazine/hydroquinidine 1,4-phathalazinediyl diether (C61) as the first and only selective inhibitor of the substrate binding P-site of SYK. The C61 NLF exhibited a very favorable pharmacokinetic and safety profile in mice, induced apoptosis in primary B-precursor ALL blast cells taken directly from patients as well as in vivo clonogenic ALL xenograft cells, destroyed the in vivo clonogenic fraction of ALL blast cells, and, at nontoxic dose levels, exhibited potent in vivo antileukemic activity against patient-derived ALL cells in xenograft models of aggressive B-precursor ALL. Our findings establish SYK as an attractive molecular target for therapy of B-precursor ALL. Further development of the C61 NLF may provide the foundation for therapeutic innovation against therapy-refractory B-precursor ALL.
Keywords: Acute Lymphoblastic-Leukemia; Protein-Kinase Inhibitors; Childrens Oncology Group; Spleen Tyrosine Kinase; Drug-Delivery; Cells; Substrate; Therapy; Relapse